La morphologie des lits des petits cours d'eau en milieu forestier tempéré : l'exemple du vallon de la Goutte de l'étang de Saloup en forêt de Tronçais (Allier, France) - Jean-Pierre Larue (Physio-Géo)
A geomorphological and sedimentological analysis of the Goutte de l'étang de Saloup watershed, in the Tronçais forest, makes it possible to show and explain the different channel morphologies in forested and non forested areas. Large woody debris have morphologic impacts that cause unequal topographies in the flood plain shaped by secondary channels, the level difference between relief and hole forms reaching 11,5 m. But the lithology and the forest long history, with forest clearing episodes, also explain the spatial morphologic variety. Thus, forest fires and clearings could have caused sandy accumulation at 1365±30 BP, date obtained from charcoal finded in the alluvial deposits. Since 1817, the Saloup dam also favoured sandy accumulation in the downstream river reaches.